Creating a library holding group: an approach to large system integration - Huffman, Isaac R.; Martin, Heather J.; Delawaska-Elliott, Basia (Journal of the Medical Library Association, 2016)
Faced with resource constraints, many hospital libraries have considered joint operations. This case study describes how Providence Health & Services created a single group to provide library services. Using a holding group model, staff worked to unify more than 6,100 nonlibrary subscriptions and 14 internal library sites. Our library services grew by unifying 2,138 nonlibrary subscriptions and 11 library sites and hiring more library staff. We expanded access to 26,018 more patrons. A model with built-in flexibility allowed successful library expansion. Although challenges remain, this success points to a viable model of unified operations.